Single daily dose corticosteroid treatment. Issue 1 (February 1976) - Myles, A B; Schiller, L F; Glass, D; Daly, J R
Abstract : Thirteen patients with rheumatoid or psoriatic arthritis who had not previously received corticosteroids were treated with prednisolone in a single-dose each morning. Insulin-hypoglycaemia tests were performed before starting steroids in each patient, and again at the conclusion of the study in twelve of the thirteen (duration of steroid treatment 8-40 m). There was no difference in the mean basal or peak levels of corticosteroids, or the mean peak of growth hormone (GH) in the tests done before or during treatment, although one patient lost GH responsiveness. There was thus no evidence of hypothalamo-pituitary-adrenal (HPA) suppression in any of the twelve patients, and there was a good therapeutic response in twelve out of thirteen. One patient was dropped from the trial because treatment failed. In contrast, of seven patients who had received a similar total dose of prednisolone twice daily, three showed HPA suppression and two had lost GH responsiveness.